Adhesion of Escherichia coli and Lactobacillus fermentum to Films and Electrospun Fibrous Scaffolds from Composites of Poly(3-hydroxybutyrate) with Magnetic Nanoparticles in a Low-Frequency Magnetic Field; International Journal of Molecular Sciences; Vol. 25, iss. 1 - Voinova V. Vera; Zhuykov V . A. Vsevolod Aleksandrovich; Zhuikova Yu. V. Yulia; Sorokina A. Anastasia; Makhina T. Tatjyana; Bonartseva G. A. Garina Aleksandrovna; Parshina E. Yu. Evgeniia; Hossain M. A. Muhammad Asif; Shaytan K. V. Konstantin Voldemarovich; Pryadko A. Artyom; Chernozem R. V. Roman Viktorovich; Mukhortova Yu. R. Yulia Ruslanovna; et al. (2024, 2024)
Title screen